2007
DOI: 10.1179/136485907x193815
|View full text |Cite
|
Sign up to set email alerts
|

A randomized and controlled comparison of the wash-resistances and insecticidal efficacies of four types of deltamethrin-treated nets, over a 6-month period of domestic use with washing every 2 weeks, in a rural area of Iran

Abstract: In a randomized, prospective, 6-month-long field study in a rural area of Iran, the wash resistances of 200 nets (40 PermaNet, 40 Yorkool and 40 A-Z nets), that their manufacturers claimed be long-lasting insecticidal nets (LLIN), were compared with those of 40 nets conventionally treated with deltamethrin (using K-O Tab tablets). All the nets were kept in routine domestic use and subjected to standardized hand-washing at 2-week intervals. Wild-caught or laboratory-reared Anopheles stephensi were used for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…In previous studies, the wash resistance of PermaNet2 was found to be similar to the results of wash resistance of PN2 (new generation of PermaNet2) up to 15 washes. 2,17,18,20,21 In the present study, the results showed better wash resistance of PN2 in comparison to PermaNet2 up to 21 washes. 21 22,23,26 In two studies that were carried out by Yates et al and Oxborough et al on wash resistance of KO 123, although their studies were laboratory based and they used WHO laboratory washing methods, they reported similar results to our study and confirmed that KO 123 is LLITNs.…”
Section: 15supporting
confidence: 59%
“…In previous studies, the wash resistance of PermaNet2 was found to be similar to the results of wash resistance of PN2 (new generation of PermaNet2) up to 15 washes. 2,17,18,20,21 In the present study, the results showed better wash resistance of PN2 in comparison to PermaNet2 up to 21 washes. 21 22,23,26 In two studies that were carried out by Yates et al and Oxborough et al on wash resistance of KO 123, although their studies were laboratory based and they used WHO laboratory washing methods, they reported similar results to our study and confirmed that KO 123 is LLITNs.…”
Section: 15supporting
confidence: 59%
“…Insecticide‐treated fabrics, including those used in combat uniforms and nets, have always been considered to represent the most promising form of protection against mosquito species of public health importance (Rozendaal, ). Currently, the only group of pesticides recommended for treating fabrics is that of pyrethroids, which includes permethrin, deltamethrin, lambdacyhalothrin, alpha‐cypermethrin, cyfluthrin and etofenprox, because they have strong insecticidal activity and low mammalian toxicity (Zaim et al ., ; World Health Organization, ; Müller et al ., ; Kayedi et al ., ). However, laboratory studies indicate that fabrics impregnated with pyrethroids do not prevent vector mosquitoes from landing and therefore mosquito vectors may obtain a bloodmeal through wide‐meshed nets or holed fabrics before knock‐down (Cooperband & Allan, ).…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic ester, non-ester and α-cyano pyrethroids, e.g. permethrin, etofenprox, deltamethrin, cyfluthrin, λ-cyhalothrin and α-cypermethrin, are recommended by the World Health Organization (WHO 2005(WHO , 2011c) at substance-specific application concentrations and are widely employed for insecticidal treatment of LLINs (Muller et al 2002;Kayedi et al 2007). Recent data showed that LLIN use may directly influence abundant mosquito population density with reduction rates up to 50 % in case that LLIN coverage rates within the affected population exceed 80 % (White et al 2011).…”
Section: Introductionmentioning
confidence: 99%